Pathogenic and genetic characterization of six Indian populations of Colletotrichum sublineolum, the causal agent of sorghum anthracnose - R.V. HIREMATH, H.C. TAILOR, U.S. KUSHWAHA, R.P. THAKUR*, K. MATHUR, V.P RAO, S. CHANDRA, S. SHIVRAMKRISHNAN, S.KANNAN; and S. INDIRA, R.R. DWIVEDI (Indian Phytopathology, 2002)
The pathogenic and genetic characterization of populations of C. sublineolum, the causal agent of anthracnose of sorghum, was investigated in isolates from 6 locations in India. Multi-location field evaluation and greenhouse tests were done on 16 sorghum lines that comprised the International Sorghum Anthracnose Virulence Nursery (ISAVN). The lines were tested in a field trial for 4-5 years (1992-96) at 6 locations: Indore, Surat, Patancheru, Dharwad, Udaipur and Pantnagar. Plants were scored for disease reaction (R/MR/S) and for disease severity (on a 1-9 scale where 1 is no lesions and 9 is >75% leaf area covered with lesions) at the soft-dough stage in the field and at the seedling stage in the greenhouse. Significant (P